Efficacy and safety of low dose rituximab in pemphigus: an updated systematic review and meta-analysis - Liu, Si-Han; Wang, Si-Hang; Zuo, Ya-Gang (Frontiers in Immunology, 2025)
ObjectiveTo evaluate the efficacy and safety of low-dose rituximab (RTX) in the treatment of pemphigus.MethodsA systematic literature search was conducted across PubMed, Embase, the Cochrane Library, and ClinicalTrials.gov to identify eligible studies. Primary efficacy outcomes included complete remission (CR), relapse rates, time to disease control (TDC), time to CR, and cumulative corticosteroid dose. Safety outcomes were assessed by meticulously documenting adverse events (AEs) and concomitant medications reported in each study.ResultsThe final analysis incorporated five comparative studies and nine single-arm studies investigating the efficacy and safety outcomes of low-dose RTX. Comparative data revealed no statistically significant differences between the high-dose and low-dose RTX groups in CR, relapse rates, TDC, time to CR, and cumulative corticosteroid dose. In single-arm studies, pooled CR and relapse rates were 63.2% and 28.6%, respectively. No fatal events were reported; however, severe AEs, including pneumonia and sepsis, were documented in the low-dose RTX cohort.ConclusionLow-dose RTX exhibited comparable clinical efficacy to high-dose RTX regimens in pemphigus management. However, clinicians should remain vigilant for potential AEs associated with low-dose RTX infusion.